The temperature dependence of magnetic susceptibility of solid oxygen: Cryocrystals - Jeżowski, A.; Litwicki, Z.; Sumarokov, V.V.; Stachowiak, P. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
Temperature dependence of magnetic susceptibility of polycrystalline oxygen samples has been measured in the range from 1 to 54 K. The measurements were performed using our home-designed SQUID-based gradiometer. The sensitivity of the instrument with respect to susceptibility reaches values of the order of 10-13. The results obtained are compared with earlier literature data.